2019
DOI: 10.1159/000501195
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cardioprotective Dexrazoxane Is Associated with Increased Myelotoxicity in Anthracycline-Treated Soft-Tissue Sarcoma Patients

Abstract: Background: Dexrazoxane (DEX) is indicated as a cardioprotective agent for breast cancer patients receiving the anthracycline doxorubicin. Two meta-analyses in metastatic breast cancer reported an apparent increase in the severity of myelosuppression when DEX was used. So far, no data in soft-tissue sarcoma (STS) patients are available. Methods: We retrospectively analyzed hematological toxicity data from 133 consecutive STS patients who received a chemotherapy regimen containing an anthracycline and ifosfamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…7,8 Unfortunately, its clinical use has been restricted due to carcinogenic potential with an increased risk for development of acute myeloid leukemia and myelodysplastic syndrome. 9,10 In recently years, oxidative stress caused by excessive production of reactive oxygen species (ROS) has been the most widely investigated and accepted mechanism of DOX induced cardiotoxicity, and natural antioxidative molecules with good e cacy and safety have attracted increasingly high attention. [11][12][13][14][15] However, drug delivery system research is still a huge challenge to realize further development and clinical application of these promising cardioprotective candidates mainly due to undesirable physico-chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Unfortunately, its clinical use has been restricted due to carcinogenic potential with an increased risk for development of acute myeloid leukemia and myelodysplastic syndrome. 9,10 In recently years, oxidative stress caused by excessive production of reactive oxygen species (ROS) has been the most widely investigated and accepted mechanism of DOX induced cardiotoxicity, and natural antioxidative molecules with good e cacy and safety have attracted increasingly high attention. [11][12][13][14][15] However, drug delivery system research is still a huge challenge to realize further development and clinical application of these promising cardioprotective candidates mainly due to undesirable physico-chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the cumulative dose of anthracycline is the main approach to preventing the cardiotoxicity, in addition, treatment with dexrazoxane (DEX), the only FDA-approved antidote, is recommended against some anthracycline-related cardiotoxicities and accidental anthracycline extravasation [5][6][7][8]. Clinical use of DEX, however, is limited due to concerns that it may increase the myelosuppressive effects of anthracyclines and ifosfamide [9] and it may also cause secondary malignancies after treatment for some pediatric cancers [10,11]. DEX (ICRF-187); is a (S)-4,4'-(1-methyl-1,2-ethanedyl) bis-2,6-piperazinedione and belongs to the bisdioxopiperazines [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although many reviews have suggested the prophylactic use of the ironchelator dexrazoxane for cardioprotection, some human studies have revealed a higher frequency of the haematological side effects of this drug (leukopenia, neutropenia, thrombocytopenia, etc.) in patients receiving AC therapy supplemented with dexrazoxane [28][29][30]. In the past, several heart failure (HF) medications (β-blockers, inhibitors of the renin-angiotensin-aldosterone system, lipid-lowering agents) were also examined in both animal models and human trials with varying success rates [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%